Conceptualisms : The Anthology of Prose, Poetry, Visual, Found, E- & Hybrid Writing as Contemporary Art - Tomasula, Steve (Book collections on Project MUSE., 2022)
"Anyone who looks beyond the bestseller lists can see that the literary landscape outside its commercial walls is just as varied as that of visual art, just as wild, just as conceptual: novels in the form of dioramas, narratives read through virtual-reality glasses, or told as a series of tweets, stories told as recipes, poems in skywriting, genetic code, pixels, skin-as well as print and sound. The 100+ prose works and poems that make up Conceptualisms all have the strangeness authors have always given ordinary speech in order to transform it into literature. In fact, this strangeness, or unfamiliarity, may be the very core of what makes writing literature, and pushed to its boundaries, what makes literature conceptual. Experimental, conceptual, avant-garde, hybrid, surfiction, fusion, radical, slip-stream, avant-pop, postmodern, self-conscious, innovative, L=A=N=G=U=A=G=E writing, alternative, anti- or new literature.... Across the years, a variety of names have been used to describe fiction, poetry and hybrid writing that, like conceptual visual art, foregrounds its ideas, explores new forms, challenges mainstream writing traditions, strives for ways to speak to the present. Along with whatever else they do, they ask, Why isn't this also literature?-and keep the boundaries of literature flexible and unresolved. Now, for the first time, here is an anthology that offers an overview of this other tradition as it lives in the early decades of the 21st century. The first major anthology of this other tradition, Conceptualisms presents writing by over 90 authors, across three generations, representing a plethora of aesthetics and approaches to their subjects. Readers will recognize authors who have shaped the nature of contemporary writing, such Lydia Davis, Charles Bernstein, Nathaniel Mackey, David Foster Wallace, and Claudia Rankine. They'll also find authors, and responses to the canon, that they haven't yet encountered. Conceptualisms is a book of ideas for writers, teachers and scholars, as well as readers who wonder how many ways literature can live"--